Study on Quantification and Toxicity Estimation of Perfluoroalkyl Substances in Vietnamese Fish and Food Packaging Materials - Hieu, Nguyen Duc; Lieu, Tran Thi; Anh, Hoang Quoc; Tuyen, Le Huu; Nghia, Nguyen Trong; Chuc, Nguyen Thi; Huong, Nguyen Thi Anh; Hoa, Nguyen Thi Quynh (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1, 2023)
In this study, concentrations of perfluroalkyl substances (PFASs) including 7 perfluorocarboxylic acids (PFCAs) and 3 sulfonates (PFSs) were determined in fresh water fish and food packaging material samples collected from Hanoi, Vietnam. Concentrations of Σ10PFASs ranged from 0.24 to 1.73 (median 0.62) ng/g wet weight for fish samples, and from not detected to 536 (median 0.98) ng/g dry weight for food packaging materials. PFAS levels in our fish samples were within low to moderate ranges compared to other countries, implying relatively low contamination degree of water environment in Hanoi. PFAS contents in almost food packaging samples were generally low (<2 ng/g), except for 3 mochi papper trays (323-536 ng/g). The sources of some longchain PFCAs (e.g., PFOA and PFDA) in a few food packaging samples were still unclear. Relative potencies (REP) of PFASs to PFOA based on thyroid hormone disruption effects were reviewed and applied to estimate toxicity equivalents (PFOA-EQs) of PFAS mixtures in analyzed samples. In term of toxicity contributions, PFOS and PFOA were the most important compounds, accounting for about 70% of PFOA-EQs.